2016
DOI: 10.1055/s-0036-1584126
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis, Ovarian Reserve and Live Birth Rate Following In Vitro Fertilization/Intracytoplasmic Sperm Injection

Abstract: Purpose To evaluate whether women with endometriosis have different ovarian reserves and reproductive outcomes when compared with women without this diagnosis undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI), and to compare the reproductive outcomes between women with and without the diagnosis considering the ovarian reserve assessed by antral follicle count (AFC). Methods This retrospective cohort study evaluated all women who underwent IVF/ICSI in a university hospital in Brazil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…We also found a significantly lower number of oocytes retrieved and mature oocytes in women with endometriosis, despite the higher gonadotropin doses used. This is in accordance with the available literature and is explained by the lower ovarian reserve in these patients [7][8][9][10][11][12]56]. Another added factor that could contribute to the lower oocyte yield is the difficult access to the follicles during retrievals in the presence of large endometriomas [57].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also found a significantly lower number of oocytes retrieved and mature oocytes in women with endometriosis, despite the higher gonadotropin doses used. This is in accordance with the available literature and is explained by the lower ovarian reserve in these patients [7][8][9][10][11][12]56]. Another added factor that could contribute to the lower oocyte yield is the difficult access to the follicles during retrievals in the presence of large endometriomas [57].…”
Section: Discussionsupporting
confidence: 88%
“…Focal loss of follicular density may cause dysregulation of folliculogenesis, with increased recruitment and atresia acting in a vicious circle, leading to a loss of the follicular capital, resulting in an overall decline in ovarian reserve. The negative effect of endometriosis on ovarian reserve and response to controlled ovarian stimulation (COS) for in vitro fertilization (IVF) has been shown by different studies [7][8][9][10][11][12], but the impact of endometriosis on the oocyte and embryo quality is still debated [13][14][15][16]. In this context, the aim of this study was to assess the impact of endometriosis on IVF cycles parameters, especially on embryo quality and IVF outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding risk of miscarriage when endometriosis is present, IVF seems to be an independent factor ( 100 ). In addition, the chance of women with endometriosis to conceive are similar to disease-free women, as identified in a previous study ( 101 ). It has been stated that women with endometriosis undergoing IVF exhibit aneuploidy percentages similar to healthy women of the IVF treatment group ( 102 ).…”
Section: Endometriosis-associated Infertilitysupporting
confidence: 79%
“…Corroborating this hypothesis, a study published by our group evaluated 787 women who underwent IVF/ICSI (241 with endometriosis and 546 without) and demonstrated that although the mean age was similar between women with and without the diagnosis of endometriosis (33.8 AE 4 versus 33.7 AE 4.4 years, respectively), poor ovarian reserve, defined as an antral follicle count 6 before the beginning of ovarian stimulation, was more common in women with endometriosis (39.8% versus 22.7%). 15 The chance of achieving live birth was similar between women with the diagnosis of endometriosis and those without it (19.1% versus 22.5%), and also when considering only women with a poor ovarian reserve (9.4% versus 8.9%) and only those with a normal ovarian reserve (25.5 versus 26.5%). Thus, we concluded that women diagnosed with endometriosis are more likely to have a poor ovarian reserve; however, their chance of conceiving by IVF/ICSI is similar to the one observed in patients without endometriosis and with a comparable ovarian reserve.…”
mentioning
confidence: 75%